Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 193316 by gatocomcirrose last updated on 10/Jun/23

  IS THIS RIGHT?  I=∫_0 ^∞ e^(−ix^2 ) dx  I^2 =∫_0 ^∞ e^(−ix^2 ) dx∫_0 ^∞ e^(−iy^2 ) dy  =∫_0 ^∞ ∫_0 ^∞ e^(−iy^2 ) dye^(−ix^2 ) dx  =∫_0 ^∞ ∫_0 ^∞ e^(−i(x^2 +y^2 )) dydx  dydx=dA=rdrdθ  I^2 =∫_0 ^(π/2) ∫_0 ^∞ e^(−ir^2 ) rdrdθ    ∫_0 ^∞ e^(−ir^2 ) rdr; u=−ir^2 ⇒du=−2irdr  −(i/2)∫_(−∞) ^0 e^u du=−(i/2)    I^2 =∫_0 ^(π/2) −(i/2)dθ=−((iπ)/4)⇒I=(√((−iπ)/4))  I=(i/2)(√(e^(iπ/2) π))=((ie^(iπ/4) )/2)(√π)  I=((i(√π))/2)(((√2)/2)(1+i))=((i(√(2π)))/4)(1+i)

ISTHISRIGHT?I=0eix2dxI2=0eix2dx0eiy2dy=00eiy2dyeix2dx=00ei(x2+y2)dydxdydx=dA=rdrdθI2=0π20eir2rdrdθ0eir2rdr;u=ir2du=2irdri20eudu=i2I2=0π2i2dθ=iπ4I=iπ4I=i2eiπ/2π=ieiπ/42πI=iπ2(22(1+i))=i2π4(1+i)

Commented by aba last updated on 10/Jun/23

wrong I=−((i(√(2π)))/4)(i+1)

wrongI=i2π4(i+1)

Answered by aba last updated on 10/Jun/23

I=(√((−iπ)/4))=(1/2)(√(e^(−i(π/2)) π))=(e^(−i(π/4)) /2)(√π)=((√(2π))/4)(1−i)=−((i(√(2π)))/4)(i+1)=(√(π/2))((1/2)−(i/2)) ✓

I=iπ4=12eiπ2π=eiπ42π=2π4(1i)=i2π4(i+1)=π2(12i2)

Answered by Mathspace last updated on 15/Jun/23

I=∫_0 ^∞  e^(−ix^2 ) dx  we do (√i)x=t ⇒  I=∫_0 ^∞  e^(−t^2 ) (dt/( (√i)))  or i=e^((iπ)/2) ⇒  (√i)=e^((iπ)/4) ⇒I=e^(−((iπ)/4)) .∫_0 ^∞  e^(−t^2 ) dt  =((1/( (√2)))−(1/( (√2)))i)×((√π)/2)  =((√π)/(2(√2)))(1−i)

I=0eix2dxwedoix=tI=0et2dtiori=eiπ2i=eiπ4I=eiπ4.0et2dt=(1212i)×π2=π22(1i)

Terms of Service

Privacy Policy

Contact: info@tinkutara.com